Hambatan Komunikasi Antarpribadi Mengenai Keterbukaan Diri pada Pengguna Akun Pseudonim (Cyber Account) di Media Twitter - Fathonah, Siti; Nursanti, Siti; Tayo, Yanti (Jurnal Publisitas, 2022)
Following the government's advice during the COVID-19 pandemic, which urges people to stay at home and avoid crowds, this has resulted in increased use of social media, one of which is twitter. Twitter is made by the community as a means to interact with other people who are considered so effective. Usually twitter users will use their personal identity in creating their accounts. However, as time goes by, currently there are some of them who become twitter users with their own identity. They will use a pseudonym where this type of user can be known as a pseudonym (cyber account). Although these pseudonymous (cyber account) users are anonymous, not many of them are self-disclosing between their fellow pseudonymous (cyber account) users. This study was conducted with the aim of knowing how the barriers to interpersonal communication in self-disclosure are intertwined with pseudonymous account users (cyber account) on Twitter. The results of this study are to see how the barriers of pseudonymous account users (cyber account) in conducting interpersonal communication regarding self-disclosure which consists of several factors: fear of self-disclosure if it is too excessive, negative perceptions of others about ourselves, self-rejection.